Lo Iuav ai Tolentini: Carlo Scarpa e gli altri Storia e documenti - BRODINI, ALESSANDRO (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2020)
The Scuola superiore di architettura di Venezia, later called Iuav, was founded in 1926. To cope with the inadequacy of the original seat in Palazzo Giustinian, during the Sixties the University moved to the complex of San Nicolò da Tolentino, known as "i Tolentini". Investigating the history of the transformations of the Renaissance monastery, the book highlights the often-overlooked contribution of Carlo Scarpa, one of the most significant figures of the Scuola, but also of other designers who contributed to outline the features of the iconic building of Iuav. The analysis is divided into two parts: the first presents the protagonists, the designs, the building works, and the management of the building site, principally on the basis of a rich amount of visual sources; the second is a collection of mostly unpublished documents, which contributes to understand the cultural climate of those years with the power of primary sources.